Psychological Factors in Temporomandibular Disorders Patients during COVID-19 Pandemic: A Cross-Sectional Study - Rocha, Thais de Oliveira [UNESP]; Oliveira, Wagner de [UNESP]; Paula, Angela Renata de [UNESP]; Oliveira, Daniela Lobo [UNESP]; Rode, Sigmar de Mello [UNESP] (Assoc Apoio Pesquisa & Saude Bucal-apesb, 2022)
Objective: To assess the influence of the COVID-19 pandemic on levels of anxiety, stress, and orofacial pain in individuals with and without TMD. Material and Methods: In this cross-sectional study, the participants were divided into two groups (n=10, each) experimental group (EG) TMD patients and control group (CG), without TMD. The presence of TMD was confirmed using the RDC/TMD. The Beck Anxiety Scale (BAI), Perceived Stress Scale (PSS), and Oral Analog Scale were used for assessment. The Beck Anxiety Scale is composed of 21 multiple-choice questions describing symptoms of anxiety, while the PSS is a measure that evaluates life situations as stressful. An Oral Analogue Scale was applied to each individual to quantify orofacial pain, with 0 (zero) without pain and 10 (ten) being the worst pain ever felt. The comparison between groups was performed using the Mann-Whitney test. Logistic regression was used to verify TMD dependence in relation to BAI and PSS-10. Quantitative variables were correlated with each other by Pearson's correlation coefficient. The level of significance considered for all tests was 5%. Results: The association was statistically significant (p <= 0.05) for BAI and PSS with a TMD. Conclusion: Although the COVID 19 pandemic has had a psychological impact on the general population, patients with TMD have higher levels of anxiety and stress than the control group.
Keywords: Coronavirus; Anxiety; Temporomandibular Joint Disorders; Psychological Distress